The research of activities of professional pharmaceutical self-government organizations abroad: uk. - Galiy, L.V.; Muzyka, T.F. (Social Pharmacy in Health Care, 2021)
Aim. To study the international experience of the activities of professional pharmaceutical self-government organizations (OPFS) on the issues of professional protection of pharmacy specialists (PS) and the possibility of its use in Ukraine. Materials and methods. During the research, a comparative analysis of the OPFS activities, data from official sites, scientific literature were used. Results. It has been found that abroad the state creates legal regulation of the OPFS activities. It is the state that takes responsibility for the activities of the pharmaceutical industry and for the list of powers for OPFS in all areas of its activities. In Ukraine, professional associations are involved in the implementation of these issues, but the lack of regulation of their relations with the governing bodies complicates their implementation. Over the past years, the foundations of the formation and functioning of OPFS, the relationship not only with the management bodies, but also with individual specialists (individuals and legal entities) have been studied. In modern conditions, each association chooses its own directions of its implementation independently since there is no clear distribution of powers. Сonclusions. According to the results of the foreign experience studies, it has been found that the main task of OPFS is to protect the rights and interests of PS, provide legal and economic advice, support the continuous professional development of PS, consider the issues of professional ethics, promote and increase the role of pharmacists in the healthcare sector, etc. These studies can be used to regulate the activities of OPFS. Key words: professional pharmaceutical self-government organizations; pharmacy specialists; pharmaceutical institutions; professional activities